(untitled) (Bangladesh Journal of Microbiology, 2016)
A microbiological study was carried out to determine the prevalence of extended spectrum beta lactamase (ESBL) producing E. coli in anorectal sepsis patients in Bangladesh. One hundred specimens of pus, swab, or exudates from anorectal sepsis cases were studied. All the 61 isolates of E. coli were found to be highly resistant to most of the drugs used. Among these, 14 multidrug resistant E. coli were examined for ESBL production by double disc diffusion method. Six of these were found to be ESBL positive. PCR analysis revealed that 3 of the 6 isolates had coexistence of blaSHV, blaOXA and blaCTXM-1 genes. Two of the isolates had only blaSHV gene, whereas 1 isolate had a combination of blaTEM and blaSHV genes. Three of these were resistant to all the drugs tested, while two were sensitive to getamicin and one to ciprofloxacin. None of the E. coli strains possessed blaCTXM-2, blaCTXM-8, blaCTXM-9, and qnr genes. Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 23-29